Prewedding in the Perspective of Islamic Law - Mohammad Syafa'ad; La Ode Ismail Ahmad; Abdul Rahman Sakka (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
In terms of meaning, a man is prohibited from being alone with a woman who is not his mahram and a woman is prohibited from traveling except with her mahram, because if she does not go with her mahram there is fear that slander or bad things will happen to the woman. However, if there is a need to leave the house, it is permissible to leave the house on condition that you maintain personal purity and maintain a sense of shame. Contextualization of the hadith prohibiting seclusion in taking pre-wedding photos, namely the hadith prohibiting seclusion is one of the hadiths that is relevant to the cultural phenomenon of pre-wedding photos. Ikhtilat, kasyful aurat, touching with the opposite sex, tabarruj and khalwat are behaviors that violate Islamic law which usually occur during pre-wedding photos. Keywords: first keyword, second keyword, third keyword